2006
DOI: 10.1002/cne.21091
|View full text |Cite
|
Sign up to set email alerts
|

Mitral cells in the olfactory bulb of adult zebrafish (Danio rerio): Morphology and distribution

Abstract: The mitral cell is the primary output neuron and central relay in the olfactory bulb of vertebrates. The morphology of these cells has been studied extensively in mammalian systems and to a lesser degree in teleosts. This study uses retrograde tract tracing and other techniques to characterize the morphology and distribution of mitral cells in the olfactory bulb of adult zebrafish, Danio rerio. These output neurons, located primarily in the glomerular layer and superficial internal cell layer, had variable-sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 80 publications
6
71
0
Order By: Relevance
“…This antibody was used for staining catecholaminergic cells in a wide range of vertebrate species from dogfish to humans. In zebrafish (McLean and Fetcho, 2004a,b;Fuller et al, 2006) and dogfish (Sueiro et al, 2003(Sueiro et al, , 2007Carrera et al, 2005) it has been shown to stain only well-characterized catecholaminergic cells consistent with known catecholaminergic neurons in other species .…”
Section: Immunocytochemistrymentioning
confidence: 94%
“…This antibody was used for staining catecholaminergic cells in a wide range of vertebrate species from dogfish to humans. In zebrafish (McLean and Fetcho, 2004a,b;Fuller et al, 2006) and dogfish (Sueiro et al, 2003(Sueiro et al, , 2007Carrera et al, 2005) it has been shown to stain only well-characterized catecholaminergic cells consistent with known catecholaminergic neurons in other species .…”
Section: Immunocytochemistrymentioning
confidence: 94%
“…However, a recent study (Fuller et al, 2006) reported a revised description of zebrafish MC morphology in which the majority of retrogradely labeled MCs have a single primary dendrite with a discrete tuft and a smaller proportion of MCs showing the multidendritic morphology also innervates a single glomerulus. This notion was supported by the present result that the vast majority of genetically labeled single MCs (31 of 32 MCs) showed the uni-dendritic morphology, innervating only a single glomerulus.…”
Section: Heterogeneity Of Mitral Cellsmentioning
confidence: 99%
“…The mitral cells located in the lateral part of the teleost OB are morphologically different from those in the medial part (Alonso et al, 1988;Fuller et al, 2006), which suggests physiological and functional distinctions. However, no differences between the medial Responses: ++, number of units responding to both skin extracts; +0, the number of units responding to the first but not the second skin extract; 0+, the number of units responding to the second but not the first skin extract; 0 0, number of units not responding to any of the two skin extracts.…”
Section: Neural Activation Induced By Various Odorants Present In Thementioning
confidence: 99%